(untitled) (Revista Latino-Americana de Enfermagem, 2010)
Adherence to chronic Oral Anticoagulant Therapy (OAT) is directly related to patients' understanding of the therapy. This study verified the knowledge of patients with mechanical valve prostheses concerning OAT. This is a contemporary cross-sectional study, the sample is composed of patients with mechanical valve prostheses (MVP) in outpatient follow-up. A 10-question instrument was used; answers were know' (1 point), know partially' (half point), or do not know' (zero). Patients were grouped according to the result obtained: ≤ 4 points was considered insufficient knowledge; >; 4 ≤ 8 equated to moderate knowledge; and >; 8 was considered appropriate knowledge. Of the 110 patients, 61.8% presented moderate knowledge, 40.9% were not able to name at least one factor that may alter the INR (International Normalized Ratio) and 37.3% were not able to report their INR target range. The majority of patients presented moderate knowledge concerning the treatment. Strategies to improve knowledge on the topic should be implemented to minimize risks.